Effect of potential on aluminium early-stage electrodeposition onto NdFeB magnet. (4th May 2017) - Jiang, L.; Jin, Z.; Xu, F.; Yu, Y.; Wei, G.; Ge, H.; Zhang, Z.; Cao, C.
Abstract : Aluminium film has been electrodeposited onto sintered NdFeB magnet at room temperature (25°C) in ionic liquid electrolytes named aluminium chloride-1-ethyl-3-methylimidazolium chloride ionic liquid (AlCl3 -EMIC). Electrodeposition mechanism of Al film is analysed using cyclic voltammetry and chronoamperometry measurements. Structure and morphology of specimen are characterised and analysed using X-ray diffraction, energy-dispersive X-ray spectrum and atomic force microscopy. The results indicate that the process of Al electrodeposition follows the three-dimensional instantaneous nucleation mechanism. As the potentials vary from −0.4 to −0.8 V, the diffusion coefficient ( D ) of and the calculated number density of Al valid nuclei sites ( N 0 ) on the sintered NdFeB magnet both increases. The deposited films consist of pure fcc phase of Al metal, and Al grains with crystal orientation of 111, 200, 220 and 311 are dominant components. Al film deposited at −0.6 V has finer and smoother surface, with the roughness value of 135.10 nm.